Analysis of the Implementation of Digital Governance in Surabaya City - Keiko Girlie Obey Yarangga; M. Daffa Viyan P; Alberth Vic Damego Pigai; Nasrul Miskul Kohar; Muhammad Yunan (International Journal of Scientific Research, 2024)
This study investigates the implementation of digital governance in Surabaya City, focusing on the electronic-based licensing system. It explores how digital governance impacts public administration efficiency and transparency while addressing bureaucratic hurdles. Significant advancements in service delivery have been noted, though challenges such as the digital divide persist. Proposed solutions include fostering interagency collaboration, staff training, and enhancing digital infrastructure to optimize technology adoption.